Colistin Susceptibility in Carbapenem Resistant Klebsiella Pneumoniae and their Ability of Biofilm Formation - Kadum, Sarab Murad (Iraqi Journal of Science, 2020)
A total of 157 clinical samples were collected from different clinical specimens (urine, sputum, blood, swabs, and cannula) from several hospitals in Iraq. Among the samples, 51 isolates (32.48%) of Klebsiella pneumoniae were identified according to morphologicaland cultural characteristics as well as the Enterosystem 18R test. Higher numbers of K. pneumoniae isolates were observed in urine samples (26, 52%) than the other samples, and in females (70.6%) than males (29.4%) (female: male ratio of about 2.4:1). Antibiotic susceptibility of K. pneumoniae against 12 commonly used antibiotics was determined through the disc-diffusion method. The results revealed a higher resistance rate in 51 isolates (100%) against Cephalexin, followed by Ceftazidime (50, 98%), while the lowest resistance rate (24, 47%) was against each of Imipenem and Meropenem. Also, the investigation of the minimum inhibitory concentration (MIC) of Colistin using E-test (strips) demonstrated that 33 isolates were resistance, as compared to 31 using the disk diffusion assay. DNA was extracted from K. pneumoniae isolates and molecularly tested using polymerase chain technique (PCR) with a specific primer and 108 bp product to detect the rpoB gene that represents this bacteria . Also, all of the 51 isolates of K. pneumoniae identified by the rpoB gene were detected for the expression of the Colistin drug resistance gene mgr-B , which was amplified (347 bp) using a specific primer. Colistin resistance gene mgr-B was amplified and sequenced from the twenty isolates. Only 6 isolates appeared with a single nucleotide substitution; G instead A, A instead G, C instead G and G instead C. Also, this study tested biofilm formation from K. pneumoniae isolates , using the microtiter plate method, in association with Colistin and Carbapenem resistant. The Colistin and Carbapenem resistance pattern was compared to the ability of biofilm-formation as weak formation versus strong and also, Multi-drug resistant isolates were more common among weak versus strong biofilm formers.